Chechnya : life in a war-torn society - Tishkov, V. A. (Valeriĭ Aleksandrovich), 1941- (California series in public anthropology, 2004)
This is an illumination of one of the world's most troubled regions from a unique perspective - that of a prominent Russian intellectual. Valery Tishkov examines the evolution of the war in Chechnya that erupted in 1994, untangling the myths and the long-held resentments that have fueled the crisis.